Anthropogenic Noise and Its Footprint on ELF Schumann Resonance Recordings - Tritakis, V.; Contopoulos, I.; Florios, C.; Tatsis, G.; Christofilakis, V.; Baldoumas, G.; Repapis, C. (Frontiers in Earth Science, 2021)
A set of various short artificial disturbances from rifle firings, car engine operation, car radio, shakings of the apparatus, etc., were generated deliberately near our ELF recording stations in order to identify their footprint on the recordings of atmospheric electromagnetic radiation in the Schumann resonance (SR) band (from about 2–50 Hz). Such disturbances simulate anthropogenic noises from hunters, hikers, campers, etc., which may occur in a remote-isolated ELF recording station. We expect that our work will assist fellow scientists to differentiate between artificial signals created from anthropogenic activity and real signals attributable to geophysical phenomena.